Comparative analysis on excerpts about Desht-i Kypchak from Al-‘Umari’s and Al-Kalkashandi’s essays - Ильясовa, З. С.; Айгумусовa, А. Т. (Journal of Oriental Studies, 2018)
In this article, comparative analysis on excerpts from Al-‘Umari’s essay “Masalik al-absar fi mamalik al-amsar” and Al-Kalkashandi’s “Subh al-a‘sha fi kitabat al-insha” was being considered. These works are the important sources on the history of Desht-i Kypchak. In the excerpts the state Desht-i Kypchak, its geography, way of life, economy, the military order of the Kypchaks and the social status of the Kypchak women are described.